From Theory to Practice: Implementing Micro-Teaching Skills on Teaching Competencies among B.Ed. Prospective Teachers (International Journal of Scientific Research in Science and Technology, 2024)
The increasing complexity of educational environments calls for highly skilled educators who are adept at employing effective teaching strategies. In response to this need, the current study explores the role of micro-teaching in enhancing teaching competencies among prospective teachers enrolled in Bachelor of Education (B.Ed.) programs. Micro-teaching, a teacher training technique that allows educators to improve their teaching skills through practice and feedback, was implemented through a carefully designed instructional program targeting a sample of 80 B.Ed. students. These students were randomly divided into two groups: an experimental group, which underwent the micro-teaching training, and a control group, which did not receive this training. To assess the impact of the micro-teaching intervention, two specific tools were utilized: the Observation cum Rating Scale for Assessing Micro-Teaching Skills and the Teaching Competencies Scale, both developed by Bawa & Nagpal in 2010. The results of the study were telling. They indicated a significant difference in teaching competencies between the experimental and control groups post-intervention. Specifically, the experimental group exhibited a marked improvement in teaching skills, demonstrating the effectiveness of micro-teaching techniques in fostering essential teaching competencies. The findings of this study substantiate the premise that micro-teaching is not just beneficial but essential for developing effective teaching competencies among prospective teachers. By simulating real-classroom scenarios, micro-teaching allows trainee teachers to refine their techniques, receive constructive feedback, and adjust their teaching behaviors in a low-risk environment. This process not only enhances their immediate teaching abilities but also contributes to their long-term professional growth. Therefore, it is concluded that integrating micro-teaching into teacher training programs can significantly elevate the quality of education provided by new teachers, better preparing them to meet the diverse needs of students in dynamic educational settings.